ABUNDANCE AND DISTRIBUTION OF PENAEID LARVAE AS AN INDEX OF PENAEID PRAWN RESOURCES OF THE INDIAN OCEAN - Paulinose, V T; George, M J (Indian Journal of Fisheries, 2011)
Andysis of the data on the abundance of larvae of penaeids in 1927plankton samples collected from the Indian Ocean during the InternationalIndian Ocean Expedition (1960-1965) has shown that these larvae are morecommonly represented in the area nearer the coast as indicated in the preliminaryobservations by Menon et al (1967).